Inorganic phosphates in juices from different parts of sugarcane stalks (cultivars ctc 9, ctc 15 and ctc 16) - Tasso Junior, Luiz Carlos [UNESP]; Silva Neto, Helio Francisco [UNESP]; Modesto Homem, Bruno Fernandes [UNESP]; Marques, Marcos Omir [UNESP] (Interciencia, 2014)
This study aimed to quantify, the inorganic phosphates in sugarcane juice from nodes and internodes of three sugarcane cultivars. The experimental design was a randomized block in factorial scheme 3x2. The main treatments were three sugarcane cultivars and two parts of the stalk (nodes and internodes). The inorganic phosphates contents were determined for each treatment. The results were subjected to variance analysis by the F test; when statistically significant, means were compared by the Tukey test at 5% probability. It is concluded that the three cultivars (CTC 9, CTC 16 and CTC 15) showed similar values regarding the content of inorganic phosphates present in the juice, and these values are considered adequate for a good performance in juice clarification. For the different parts of the stem, differences were observed in the levels of the nutrient studied, which showed a higher concentration in the node than in the internode.